Implementasi Media Belajar Audio Visual Film Animasi Untuk Meningkatkan Pemahaman Siswa Dalam Mengenal Ashabul Kahfi Pada Mata Pelajaran Akidah Akhlak Kelas VII MTS. Tarbiyah Waladiyah Pulau Banyak Kecamatan Tanjung Pura Kabupaten Langkat - Muhizar Muchtar, Muhammad Saleh, Laily Ramadhana Bancin, (Invention: Journal Research and Education Studies, 2021)
The results of the understanding obtained by students of class VIIC MTS Tarbiyah Waladiyah Pulau Banyak Village for the 2021/2022 academic year on the subject matter of moral aqidah the average value is still low, the class average value only reaches 58,20 while the KKM value set by the school is 75. This is because in terms of delivering moral aqidah lessons, teachers tend to use simple media so that they do not involve students actively in learning activities. Learning with media Audio Visual Animated Film can be used as an alternative learning Media in an effort to improve students' understanding of material Ashabul Kahf on the subject of moral aqidah. This media is directed to students' understanding of active learning, which involves students actively in learning activities so that students are better able to understand the material, and learning activities of aqidah and morals become more fun. This type of research is classroom action research with planning, implementation, observation, and reflection steps carried out in two cycles. The subjects of this study were students of class VIIC MTS Tarbiyah Waladiyah Pulau Banyak village, totaling 16 students. The object of this research is to increase the understanding of the moral aqidah subjects for material Ashabul Kahf through learning media Audio Visual Animated Film. Data collection techniques used in the form of tests, documentation and observations of students. Research that has been carried out on students of class VII C MTS Tarbiyah Waladiyah Pulau Banyak Village shows the results that the use ofLearning media Audio Visual Animation Film can improve students' understanding of moral aqidah subjects Ashabul Kahf's. In the first cycle there were 10 students who completed or 63% and those who had not completed 6 or 37% with a class average of 66.25, the second cycle that completed 16 students or 100% and the average class was 83.63.